2022
DOI: 10.1002/agm2.12205
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in geriatric patients with poor performance status small cell lung cancer: Series from a tertiary care center

Abstract: The mean age of the group was 65.2 (60-69) years. Three patients were females. All of them presented to us with stage 4 disease and with an ECOG-PS of 4. Two patients had chronic obstructiveThis is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Both regimens might be an option that can be preferred in the fragile geriatric age group. Furthermore, these results with geriatric SCLC patients were comparable with the younger ones with platinum+etoposide groups of pivotal trials [9] In the study by Caprario et [15]. Similar to the above studies, we found the median OS as 8.2 months in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Both regimens might be an option that can be preferred in the fragile geriatric age group. Furthermore, these results with geriatric SCLC patients were comparable with the younger ones with platinum+etoposide groups of pivotal trials [9] In the study by Caprario et [15]. Similar to the above studies, we found the median OS as 8.2 months in our study.…”
Section: Discussionsupporting
confidence: 91%